2020
DOI: 10.4018/ijt.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

Information Privacy and Emerging Technologies in the UAE

Abstract: The rapid developments of emerging technologies, including Big Data, Cloud Computing, and Internet of Things, are causing many societies to struggle whilst trying to keep up with, and adopt them. As a consequence, serious concerns and issues are being raised. The threat to personal information privacy is one of these issues. This review paper briefly introduces the aforementioned technologies and explores concepts related to concerns on information privacy and disclosure in the U.A.E. in the context of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Anis Dwiastanti et al (2020) observed that efficient financial literacy and management and motivation lead to business sustainability [2]. Bregman et al (2020) ascertained that self-efficacy and opportunity identification lead to entrepreneurs sustainability [5].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Anis Dwiastanti et al (2020) observed that efficient financial literacy and management and motivation lead to business sustainability [2]. Bregman et al (2020) ascertained that self-efficacy and opportunity identification lead to entrepreneurs sustainability [5].…”
Section: Review Of Literaturementioning
confidence: 99%